Fermented strawberry pomace enhances carcass characteristics and meat quality by regulating plasma biochemical indices and antioxidant capacity in aged laying hens - Lan, Wei; Chen, Ting; Qin, Binghua; Azad, Md. Abul Kalam; Li, Zhihua; Cui, Yadong; Kong, Xiangfeng (Frontiers in Nutrition, 2025)
IntroductionStrawberry pomace, a byproduct of strawberry processing, is rich in vitamins, polyphenols, and other bioactive compounds that may confer beneficial effects on laying hens. This study systematically evaluated how dietary supplementation with fermented strawberry pomace (FSP) modulates carcass characteristics, meat quality, and plasma parameters (lipid profiles and antioxidant capacity) in aged laying hens.MethodsThe study comprised 320 healthy 345-day-old laying hens, which were randomly assigned to four dietary groups receiving 0, 0.25, 0.5%, or 1.0% FSP for 9 weeks.ResultsThe 0.25% FSP group showed increased dressing percentage (p < 0.05) compared to other groups. FSP supplementation at 0.25–1% reduced breast muscle pH at 48 h post-slaughter, as well as 48 h drip loss. An elevation in leg muscle a* values (p < 0.05) was observed in both 0.25 and 0.5% FSP groups compared with the control group, while L* value was higher (p < 0.05) in the 0.25% FSP group compared to the 0.5% FSP group. The 0.5% FSP group showed higher leg muscle pH at 45 min (p < 0.05) than the control and 0.25% FSP groups. Plasma total antioxidant capacity (T-AOC) was enhanced (p < 0.05) in the 1% FSP group compared to the control and 0.25% FSP groups. The 1% FSP group had a higher plasma GLU level (p < 0.05) compared with other groups. The plasma FFA level was decreased (p < 0.05) in all treatment groups than the control group. All FSP groups exhibited a decreasing trend in plasma TG level (p = 0.057). In breast muscle, MDA level was lower (p < 0.05) in the 0.25% FSP group compared to the 1% FSP group. In addition, the expression of SOD1 in breast muscle was up-regulated (p < 0.05) in the 0.5% FSP group compared to the 0.25% FSP group.DiscussionCollectively, dietary FSP supplementation increased carcass characteristics and meat quality by enhancing antioxidant capacity and plasma lipid metabolism in aged laying hens. The low-dose FSP level showed the most favorable outcomes.